Utilizing Benzotriazole and Indacenodithiophene Units to Construct Both Polymeric Donor and Small Molecular Acceptors to Realize Organic Solar Cells With High Open-Circuit Voltages Beyond 1.2 V - Tang, Ailing; Chen, Fan; Xiao, Bo; Yang, Jing; Li, Jianfeng; Wang, Xiaochen; Zhou, Erjun (Frontiers in Chemistry, 2018)
Devolopment of organic solar cells with high open-circuit voltage (VOC) and power conversion efficiency (PCE) simutaniously plays a significant role, but there is no guideline how to choose the suitable photovoltaic material combinations. In our previous work, we developed “the Same-Acceptor-Strategy” (SAS), by utilizing the same electron-accepting segment to construct both polymeric donor and small molecular acceptor. In this study, we further expend SAS to use both the same electron-accepting and electron-donating units to design the material combination. The p-type polymer of PIDT-DTffBTA is designed by inserting conjugated bridge between indacenodithiophene (IDT) and fluorinated benzotriazole (BTA), while the n-type small molecules of BTAx (x = 1, 2, 3) are obtained by introducing different end-capped groups to BTA-IDT-BTA backbone. PIDT-DTffBTA: BTAx (x = 1–3) based photovolatic devices can realize high VOC of 1.21–1.37 V with the very small voltage loss (0.55–0.60 V), while only the PIDT-DTffBTA: BTA3 based device possesses the enough driving force for efficient hole and electron transfer and yields the optimal PCE of 5.67%, which is among the highest value for organic solar cells (OSCs) with a VOC beyond 1.20 V reported so far. Our results provide a simple and effective method to obtain fullerene-free OSCs with a high VOC and PCE.